FREQUENCY AND COMPARISON OF SEROEPIDEMIOLOGY HSV AND CMV IN WOMEN WITH NATURAL CHILDBIRTH AND ABORTION IN SHAHID BEHESHTI HOSPITAL, ABADAN, IRAN - Jomehzadeh, N.; Shahi, F.; Kooti, S.; Gorjian, Z.; Abdollahi L19orestani, H.; Tamimi, A.; Sobhani, A.; Khoshnood, S. (University of Eloued جامعة الوادي, 2017)
Background: Cytomegalovirus and Herpes simplexvirus are one of the most common causes of congenital infections. Objectives: The purpose of this study was to determine the seroprevalence of herpes simplex virus type 1 (HSV-1), type 2 (HSV-2) and CMV antibody in pregnant women admitting to antenatal care clinic of Shahid Beheshti Hospital in Abadan, Iran. Serum samples were collected during the study. Methods: The enzyme-linked immunosorbent assay was used to detect anti-HSV-1, anti-HSV-2 type and anti- CMV. Socio-demographic and obstetric characteristics were used for further study. Results:Â Between January and December 2016, we have studied 325 pregnant women referred to Shahid Beheshti Hospital. The mean of womenâ€™s age was 27.66 Â± 5.96 years old (range 16 to 43 years). Of the 325 participants in this study, 40 (12.3 %) were HSV-1 seropositive, 78 (24%) were HSV-2 seropositive and 36 (11%) were CMV seropositive. A combined analysis was performed for HSV-1 and HSV-2: the percentages of individuals testing regarding both HSV-1 and HSV-2 negative, both HSV-1 and HSV-2 positive, were 207 (63.7%) and 4 (1.2%) respectively.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Herpes simplex virus type 1 and type 2, Cytomegalovirus, Pregnancy, Neonatal herpes.